Penerapan Kebijakan Pengawasan Obat Tradisional dalam Perspektif Kesehatan Masyaraat - Juliana, Juliana; Kurniawan, I Gede Agus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Traditional medicine is one part of Indonesia's rich culture that has been used by the community for a long time. However, issues surrounding the safety and efficacy of traditional medicines often arise as a concern in the public health domain. This research uses qualitative research methods. The data collection technique was carried out by literature study and from interviews with traditional medicine users, traditional healthcare practitioners, and health officials. Thus, this can assist researchers in understanding their perceptions, experiences, and viewpoints regarding traditional medicine supervision. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. This is done to ensure that the implementation of legal supervision of traditional medicines is carried out through various stages. The process begins with the granting of production licenses to producers after fulfilling predetermined requirements. After that, the Food and Drug Monitoring Agency (BPOM) is responsible for supervising the production process directly on site. Supervision of the production process is carried out at least once a year. However, if there are violations of either CPOTB (Good Traditional Medicine Manufacturing Practice) or GMP (Good Manufacturing Practice) requirements, the inspection will be more intensive. The inspection is carried out until the manufacturer corrects and improves production activities in accordance with applicable standards.